Effects of a Tailored Positive Psychology Intervention on Well-Being and Pain in Individuals With Chronic Pain and a Physical Disability: A Feasibility Trial. Issue 1 (January 2016) - Müller, Rachel; Gertz, Kevin J.; Molton, Ivan R.; Terrill, Alexandra L.; Bombardier, Charles H.; Ehde, Dawn M.; Jensen, Mark P.
Abstract : Objectives: To determine the feasibility, acceptability, and efficacy of a computer-based positive psychology intervention in individuals with a physical disability and chronic pain. Methods: Individuals with spinal cord injury, multiple sclerosis, neuromuscular disease, or postpolio syndrome and chronic pain were randomly assigned to a positive psychology or a control condition. Participants in the intervention group were instructed to practice 4 personalized positive psychology exercises. Participants in the control group were instructed to write about life details for 8 weeks. Participants completed online well-being and pain-related questionnaires at baseline, posttreatment, and at the 2.5-month follow-up, and rated treatment satisfaction at posttreatment. Results: Ninety-six participants were randomized and 68 (70%) completed follow-up assessments. Participants in the positive psychology intervention group reported significant pretreatment to posttreatment improvements in pain intensity, pain control, pain catastrophizing, pain interference, life satisfaction, positive affect, and depression. Improvements in life satisfaction, depression, pain intensity, pain interference, and pain control were maintained to the 2.5-month follow-up. Participants in the control group reported significant pretreatment to posttreatment improvements in life satisfaction, and pretreatment to follow-up improvements in pain intensity and pain control. Significant between-group differences, favoring the treatment group, emerged for pretreatment to posttreatment improvements in pain intensity and pain control. Participants were similarly satisfied with both treatments. Discussion/Conclusions: The results support the feasibility, acceptability, and potential efficacy of a computer-based positive psychology intervention for improving well-being and pain-related outcomes in individuals with physical disabilities and chronic pain, and indicate that a full trial of the intervention is warranted.